Espectrometria de emissão óptica com plasma indutivamente acoplado aliada à quimiometria na determinação de íons metálicos no molusco Mytella falcata para discriminação de estuários potiguares - Brito, George Queiroz de (2010)
This work examined the possibility of using mussel Mytella falcata as bioindicator sample to detect metal ions in several estuaries potiguares, since species substances that accumulate in their tissues due to its characteristics filter feeders have been used for environmental monitoring. The chemometrics by principal components analysis was used to reduce the size of the original data in order to establish a pattern of distribution of metal ion. Samples were collected at three different points in the estuaries Curimataú, Guaraíra-Papeba, Potengi, Galinhos-Guamaré and Piranhas-Assu having been marked with the location using GPS (Global Positioning System). The determination of humidity content and digestion of the samples were performed using methods described in the Compendium of analytical standards of the Institute Adofo Lutz (2005) and the determination of metal ions of the elements Al, Ba, Cd, Cr, Cu, Mn, Ni, Pb, Sn and Zn were performed by optical emission spectrometry with inductively coupled plasma as described by USEPA method 6010C. The results show that it is possible to use this molluscum Mytella falcata in the estuaries of Rio Grande do Norte for the determination of metal ions. The data were subjected to principal components analysis (PCA) which enabled us to verify the distribution pattern of the metal ions studied in several estuaries potiguares and group them according to the metal ions in common with and relate them to the activities in each region